Rezerwy w polskich bankach - Kopiński, Adam (Reserves in Polish banks, 2008)
The article presents the rationale for reserves establishment in Polish banks, on the basis of recent regulations which embrace in the first place the attempt to reduce banking risk. Thé author characterizes the obligatory reserve, intentional reserve and the general reserve, the guidelines and rules of their creation, means of their sustenance and subsequently termination, as well as their role in the shape of bank costs and returns.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 192-198